Nurtureshock : new thinking about children - Bronson, Po, 1964-; Merryman, Ashley (New York : Twelve, 2009)
The authors discuss the inverse power of praise, why insufficient sleep adversely affects kids' capacity to learn, why white parents don't talk about race, why kids lie, why evaluation methods for "giftedness" and accompanying programs don't work, and why siblings really fight.
Includes bibliographical references (p. [265]-327) and index.
Keywords: Child development; Child psychology; Child rearing; Parenting